Ecto-5′-Nucleotidase Activity in Human T Cell Subsets. DECREASED NUMBERS OF ECTO-5′-NUCLEOTIDASE POSITIVE CELLS FROM BOTH OKT4(+) AND OKT8(+) CELLS IN PATIENTS WITH HYPOGAMMAGLOBULINEMIA - Thompson, Linda F. (1983)
T lymphocytes from control subjects were separated into subsets using monoclonal antibodies of the OKT series and complement lysis and analyzed for ecto-5′-nucleotidase activity both by quantitative radiochemical assay and a histochemical stain. T cells from 15 control subjects contained 54±4% OKT4(+) (helper/inducer) cells and 32±3% OKT8(+) (cytotoxic/suppressor) cells. Total T cell ecto-5′-nucleotidase activity was 10.9±2.1 nmol/h per 10(6) cells with 25±7% positive by histochemical stain. Ecto-5′-nucleotidase activity in OKT4-enriched populations was 5.43±1.8 nmol/h per 10(6) cells with 14±2% positive by histochemical stain; that in OKT8-enriched populations was 17.1±5.9 nmol/h per 10(6) cells with 35±8% positive by histochemical stain. Two of four patients with congenital agammaglobulinemia and four of seven patients with common variable immunodeficiency had decreased proportions of OKT4(+) T cells with corresponding increases in the proportions of OKT8(+) T cells (OKT4/OKT8 = 0.60 to 1.0 as compared with 1.7±0.2 for control subjects). All four patients with congenital agammaglobulinemia, and three of seven patients with common variable immunodeficiency also had low T cell ecto-5′-nucleotidase activity (<5.5 nmol/h per 10(6) cells). Ecto-5′-nucleotidase activity in OKT4- enriched populations isolated from four patients with low total T cell activity was 2.85±0.90 nmol/h per 10(6) cells with 10±4% positive by histochemical stain; that in OKT8-enriched populations was 6.82±1.7 nmol/h per 10(6) cells with 7.5±3% positive by histochemical stain. Thus, the number of ecto-5′-nucleotidase positive cells is decreased, especially in the OKT8(+) subpopulation, and the low total T cell ecto-5′-nucleotidase activity seen in these patients is due to fewer positive cells rather than to substantially less activity per cell. Our data indicate that ecto-5′-nucleotidase activity defines two subpopulations of T lymphocytes (ecto-5′-nucleotidase positive and negative), the proportions of which are markedly altered in many patients with hypogammaglobulinemia. In preliminary studies with seven patients, increased numbers of ecto-5′-nucleotidase negative T cells appeared to correlate with increased suppressor T cell activity toward in vitro immunoglobulin synthesis. Therefore, ecto-5′-nucleotidase may be a useful cell surface marker in the study of imbalances of regulatory T cell subsets in patients with antibody synthesis disorders.